2017
DOI: 10.20867/tosee.04.43
|View full text |Cite
|
Sign up to set email alerts
|

Co-Creating Tourist Experiences to Enhance Customer Loyalty and Travel Satisfaction

Abstract: Purpose -The purpose of this paper is to highlight the need for cooperation between tourists and travel professionals in creating a memorable visitor experience. The objectives of the study are twofold: first, to explain the concept of tourist experience co-creation and, second, to explore the relationships among tourist experience co-creation, customer satisfaction, overall travel satisfaction and customer loyalty towards travel professionals. Methodology -The study uses constructs from past literature. A sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
1
9
0
5
Order By: Relevance
“…A higher percentage of the visitors were first-time visitors to these sites, which is in line with Ma et al (2018), who reported a majority of the respondents of Dinghushan National Nature Reserve as first-time visitors. These visitors travel primarily for pleasure/ holiday with their family members, friends and spouses, as supported by Lončarić et al (2017) in his findings that visitors mostly travelled with a partner, friends or family members. This has a tendency to promote strong family bonds, thereby reducing the rate of divorce and family chaos, as visitors do not like to travel alone.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A higher percentage of the visitors were first-time visitors to these sites, which is in line with Ma et al (2018), who reported a majority of the respondents of Dinghushan National Nature Reserve as first-time visitors. These visitors travel primarily for pleasure/ holiday with their family members, friends and spouses, as supported by Lončarić et al (2017) in his findings that visitors mostly travelled with a partner, friends or family members. This has a tendency to promote strong family bonds, thereby reducing the rate of divorce and family chaos, as visitors do not like to travel alone.…”
Section: Discussionmentioning
confidence: 61%
“…This has a tendency to promote strong family bonds, thereby reducing the rate of divorce and family chaos, as visitors do not like to travel alone. A majority of the visitors also organized their travel independently, as supported by Lončarić et al (2017)…”
Section: Discussionmentioning
confidence: 99%
“…According to co-creation theory and s-d logic, a tourist is an active participant rather than a passive recipient. Therefore, both service providers and tourists have to collaborate in order to provide experience value for the tourists (Lončarić, Perišić Prodan, & Dlačić, 2017). As argued by Mathis (2013, p. 11), the tourist experience of co-creation includes the following: (1) the collaboration between the service provider and the tourist; (2) the co-production of new and improved products/services; (3) a shift away from a goods-dominant logic towards a service-dominant logic; (4) adaptability, personalisation, and uniqueness.…”
Section: Resultsmentioning
confidence: 99%
“…Co-creation of the tourist experience has mainly been explored from a theoretical perspective. Grissemann and Stokburger-Sauer (2012) and Lončarić et al (2017) point out that empirical evidence of co-creation research in tourism remains scarce and a number of research questions are still unanswered.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%